Adherence to Continuous Positive Airway Pressure Therapy in Pediatric Patients with Obstructive Sleep Apnea: A Meta-Analysis - Sawunyavisuth B; Ngamjarus C; Sawanyawisuth K (Dove Medical Press, 2023)
Bundit Sawunyavisuth,1 Chetta Ngamjarus,2 Kittisak Sawanyawisuth3 1Department of Marketing, Faculty of Business Administration and Accountancy, Khon Kaen University, Khon Kaen, Thailand; 2Department of Epidemiology and Biostatistics, Faculty of Public Health, Khon Kaen University, Khon Kaen, Thailand; 3Department of Medicine, Faculty of Medicine, Khon Kaen University, Khon Kaen, ThailandCorrespondence: Kittisak Sawanyawisuth, Department of Medicine, Faculty of Medicine, Khon Kaen University, Khon Kaen, 40002, Thailand, Tel +66-43-363664, Fax +66-43-348399, Email kittisak@kku.ac.thIntroduction: Obstructive sleep apnea (OSA) is a public health problem that affects children. Although continuous positive airway pressure (CPAP) therapy is effective, the CPAP adherence rate in children is varied. This study aimed to evaluate the CPAP adherence rate and factors associated with CPAP adherence in children with OSA using a systematic review.Methods: The inclusion criteria were observational studies conducted in children with OSA and assessed adherence of CPAP using objective evaluation. The literature search was performed in four databases. Meta-analysis using fixed-effect model was conducted to combine results among included studies.Results: In all, 34 studies that evaluated adherence rate and predictors of CPAP adherence in children with OSA were included, representing 21,737 patients with an average adherence rate of 46.56%. There were 11 calculations of factors predictive of CPAP adherence: age, sex, ethnicity, body mass index, obesity, income, sleep efficiency, the apnea-hypopnea index (AHI), severity of OSA, residual AHI, and lowest oxygen saturation level. Three different factors were linked to children with adherence and non-adherence to CPAP: age, body mass index, and AHI.Conclusion: The CPAP adherence rate in children with OSA was 46.56%. Young age, low body mass index, and high AHI were associated with acceptable CPAP adherence in children with OSA.Keywords: age, body mass index, apnea-hypopnea index